2006
DOI: 10.1051/rnd:2006003
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology and pathogenesis of cystic ovarian follicles in dairy cattle: a review

Abstract: -Cystic ovarian follicles (COF) are an important ovarian dysfunction and a major cause of reproductive failure in dairy cattle. Due to the complexity of the disorder and the heterogeneity of the clinical signs, a clear definition is lacking. A follicle becomes cystic when it fails to ovulate and persists on the ovary. Despite an abundance of literature on the subject, the exact pathogenesis of COF is unclear. It is generally accepted that disruption of the hypothalamo-pituitary-gonadal axis, by endogenous and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
231
2
20

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(304 citation statements)
references
References 109 publications
9
231
2
20
Order By: Relevance
“…In academic literature, it is debated whether ovarian follicular cysts (OFC) in dairy cows should be considered pathological or innocuous (Vanholder et al 2006). Up to the 1980s, classic clinical signs in cows with OFC as described in the literature were: short cycles, irregular estrus, nymphomania, masculinization, and relaxation of the pelvic ligaments (Kesler and Garverick 1982).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In academic literature, it is debated whether ovarian follicular cysts (OFC) in dairy cows should be considered pathological or innocuous (Vanholder et al 2006). Up to the 1980s, classic clinical signs in cows with OFC as described in the literature were: short cycles, irregular estrus, nymphomania, masculinization, and relaxation of the pelvic ligaments (Kesler and Garverick 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Up to the 1980s, classic clinical signs in cows with OFC as described in the literature were: short cycles, irregular estrus, nymphomania, masculinization, and relaxation of the pelvic ligaments (Kesler and Garverick 1982). However, dairy cows that currently develop OFC only present anestrus (Peter 2004, Vanholder et al 2006. Therefore, this ovarian condition is more often referred to as ovarian follicular cysts, and less as cystic ovarian disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possibly, the stress contributes with the formation of the CFD in sows (Scholten & Liptrap 1978). Some researchers cite endocrine disorders affecting the hypothalamo-hypophyseal axis related to development of the ovarian cysts in sows (Scholten & Liptrap 1978) and cows (Garverick 1997, Silvia et al 2002, Vanholder et al 2006. Recent investigation revealed that apoptosis and cell proliferation were altered in swine cystic follicles (Sun et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Follicular cysts in dairy cattle are defined as follicles with a diameter greater than or equal to 2 cm that are present on one or both ovaries in the absence of any luteal tissue and that clearly interfere with normal ovarian cyclicity [1]. The condition has a huge negative impact on fertility and overall productivity, owing to its effects on reproductive parameters such as calving to conception interval, number of services per conception, and pregnancy rate [2,3].…”
Section: Introductionmentioning
confidence: 99%